Legumes in cropping systems - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
A three week course on 'Legumes in Tropical and Subtropical Cropping Systems' is to be organized by the University of Hohenheim, West Germany, commencing January 9, 1989. This interdisciplinary course will present and discuss recent developments...